CURRENT TRENDS ON MATERIALS AND METHODS FOR TEETH WHITENING - Maria Mirabela IANCU; Cristiana Ioana TATIA; Alina ROBU; Marius Lucian VASILESCU; Iulian ANTONIAC; Anca Maria FRATILA (European Journal of Materials Science and Engineering)
The purpose of teeth whitening is the removal of intrinsic or extrinsic discoloration via mechanical or chemical techniques that restore the teeth to their natural shade or lighten it, depending on the chosen method. Both the abrasive particles used in mechanical procedures and the oxidant agents applied in chemical bleaching are effective if they are used according to the stain aetiology, however, the risks associated with these products (e.g. potential tooth wear, sensitivity, damage of the enamel or dentin organic matrix) are not negligible. As a response to these issues, current research in the tooth whitening field is directed towards the development of safer whitening products such as dentifrices with lower abrasive index, natural bleaching agents, or laser-assisted whitening procedures that require shorter exposure time for optimal results. This review aims to provide a description of the currently available teeth whitening techniques and their limitations, as well as the novel alternatives that promise similar or superior results with less potential side effects. For a better understanding of the subject, the structure of the tooth, the causes of teeth discoloration as well as the mechanisms of action and chemistry behind the abrasive agents and peroxide-based whitening processes were also discussed.